I. I. KOZLOV IN THE HISTORY OF THE RUSSIAN RECEPTION OF T. MOORE’S POEM «THOSE EVENING BELLS» - Zhatkin, Dmitry; Yashina, Tatiana (Revista Inclusiones, 2019)
The article is dedicated to the characteristics’ identifying of the perception of Thomas Moore’s poem «Those Evening Bells» from the poetic cycle «Selection of Popular National Airs» created by the talented representative of Russian poetry, translator of many English authors I.I. Kozlov. From a methodological point of view, the article is based on a historical-literary approach to the subject of study, combined with a comparative historical and formal methods of analyzing literary works. The basic statements of A.V. Fedorov’s linguistic theory of translation, the theory of M.M. Bakhtin about the dialogue and «stranger's word», historical, literary and theoretical works of such leading Russian literary scholars as V.M. Zhirmunsky, M.P. Alekseev, B.V. Tomashevsky, Yu.M. Lotman, V.N. Toporov, Yu.D. Levin, E.G. Etkind, devoted to the issues of comparative research of literatures and cultures, Russian–English literary connections, theory and history of literary translation are taken into account. I.I.Kozlov's romance «Evening Bells», an interpretation of Thomas Moore’s poem «Those Evening Bells», received many direct responses in the creative work of Russian poets. Thanks to the Russian color, special melodiousness and tonality, which gave the «melody» an unusual sound, the work of the English bard was put to music and offered for public performance. The characteristic melodiousness and Russian origins of the Moore’s «melody» inspired I.I. Kozlov to create the romance «Evening Bells», which was characterized by the artistic reflection of the new-founded creative details of the English poet and gained popularity in Russia thanks to the music of the Russian composer A.A. Alyabyev. Having firmly entered into the Russian song repertoire, I.I. Kozlov's «Evening Bells» was sometimes perceived by his contemporaries as a completely independent, original work. Some attempts were also made to find Russian and other sources of this work, in particular, to relate the English original with the translation of the church song of the Georgian writer Georgy Mtatsmindeli. Having gained popularity at the turn of the 1820– 1830s, I.I.Kozlov's poem «Evening Bells» was added to the list of the best works of the poet, on the basis of which the aesthetic tastes of the readers, who appreciated the interpreter's linguistic sensitivity and the variety of poetical expressive means used by him.